Examining Religious Leaders’ Engagement in Child Protection in Dzemeni, Volta Region, Ghana - Ebenezer Tetteh Kpalam; Emmanuel Nyarko-Tetteh; Eva Ahiataku (E-Journal of Humanities, Arts and Social Sciences)
It is reported that ninety-four percent of children experience some form of abuse in Ghana. Where child abuse exists, an appropriate response is child protection. Dzemeni, a fishing community in the Volta Region of Ghana is noted to have a history of high prevalence of child abuse, trafficking, child labour, and exploitation. This study aims to explore the perspectives of religious leaders on child abuse and analyse efforts by religious leaders, including inter-religious engagements for child protection in Dzemeni. Using a qualitative approach, data was collected from 15 religious leaders, comprising eight clergy, four traditional leaders and three Muslim leaders. The results showed that, although religious leaders understood the concept of child protection and undertook measures such as education of the public and provision of psychosocial support for abused children, there were no inter-religious efforts towards child protection in the community. The paper posits that inter-religious engagements for child protection could contribute significantly to the prevention of child abuse in Dzemeni.